A comparative forensic analysis of privacy enhanced web browsers and private browsing modes of common web browsers. (2018) - Gabet, Ryan M.; Seigfried-Spellar, Kathryn C.; Rogers, Marcus K.
Growing concerns regarding internet privacy has led to the development of enhanced privacy web browsers. The authors conducted a digital forensic examination, to determine the recoverable artefacts of three enhanced privacy web browsers (Dooble, Comodo Dragon and Epic) and three commonly used web browsers in anonymous browsing mode (Chrome, Edge and Firefox). In addition, the authors compared two digital forensic tools (FTK and Autopsy) commonly used by law enforcement to determine differences in recoverable browser artefacts. Results indicated the enhanced privacy browsers performed about the same as the common browsers in anonymous browsing mode. In addition, FTK was the better tool for recovering and viewing browser artefacts for both browser groups. Overall, this study did not produce sufficient evidence to conclude enhanced privacy browsers do indeed provide better privacy.